Positive solutions for elastic beam equations with nonlinear boundary conditions and a parameter

  • Wenxia Wang1Email author,

    Affiliated with

    • Yanping Zheng1,

      Affiliated with

      • Hui Yang1 and

        Affiliated with

        • Junxia Wang1

          Affiliated with

          Boundary Value Problems20142014:80

          DOI: 10.1186/1687-2770-2014-80

          Received: 7 October 2013

          Accepted: 26 March 2014

          Published: 9 April 2014

          Abstract

          This paper is concerned with the existence, nonexistence, and uniqueness of convex monotone positive solutions of elastic beam equations with a parameter λ. The boundary conditions mean that the beam is fixed at one end and attached to a bearing device or freed at the other end. By using fixed point theorem of cone expansion, we show that there exists λ λ > 0 such that the beam equation has at least two, one, and no positive solutions for 0 < λ λ , λ < λ λ and λ > λ , respectively; furthermore, by using cone theory we establish some uniqueness criteria for positive solutions for the beam and show that such solution x λ depends continuously on the parameter λ. In particular, we give an estimate for critical value of parameter λ.

          MSC:34B18, 34B15.

          Keywords

          elastic beam equation positive solution fixed point cone

          1 Introduction and preliminaries

          In this paper, we consider the following nonlinear fourth-order two-point boundary value problem (BVP) for elastic beam equation:
          { x ( 4 ) ( t ) = λ f ( t , x ( t ) ) , 0 < t < 1 , x ( 0 ) = x ( 0 ) = x ( 1 ) = x ( 1 ) + q ( x ( 1 ) ) = 0 ,
          (1)

          where λ 0 is a parameter. Throughout this paper, we assume that f C ( [ 0 , 1 ] × R + , R + ) , q C ( R + , R + ) , R + = [ 0 , + ) . x C [ 0 , 1 ] is called a positive solution of BVP (1) if x is a solution of BVP (1) and x ( t ) > 0 , 0 < t < 1 . A convex monotone positive solution means convex nondecreasing positive solution.

          Because of characterization of the deformation of the equilibrium state, fourth-order boundary value problems for elastic beam equations are extensively applied to mechanics and engineering; see [13]. Some nonlinear elastic beam equations have been studied extensively. For a small sample of such work, we refer the reader to the work of Bai and Wang [4], Bai [5], Bonanno and Bellaa [6], Li [7], Liu and Li [8], Liu [9], Ma and Xu [10], and Ma and Thompson [11] on an elastic beam whose two ends are simply supported, the works of Yang [12] and Zhang [13] on an elastic beam of which one end is embedded and another end is fastened with a sliding clamp, and the work of Graef et al. [14] on multipoint boundary value problems.

          BVP (1) with q ( x ) 0 is called a cantilever beam equation, it describes the deflection of the elastic beam fixed at the left end and free at the right end. Existence and multiplicity of positive solutions of cantilever beam problems without parameter have been studied by some authors; see Yao [15, 16] and references therein. BVP (1) with q ( x ) 0 describes the deflection of the elastic beam fixed at the left end and attached to a bearing device given by the function −q at the right end. When the elastic beam equation does not contain parameter λ, the existence of multiple positive solutions and unique positive solution was presented in [17] by variational methods and in [18] by a fixed point theorem, respectively; monotone positive solutions were obtained by using the monotone iteration method in [19]. However, there are few papers concerned with positive solutions for BVP (1) with parameter, especially with the solution’s dependence on parameter λ in the existing literature. The aim of this paper is to show that the existence and number of convex monotone positive solutions of BVP (1) are affected by the parameter λ.

          The paper is organized as follows. In Section 2, we present that a nontrivial and nonnegative solution of BVP (1) is convex monotone positive solution. In Section 3, we obtain some results on the existence, multiplicity and nonexistence of positive solutions for BVP (1). These results show that the number of positive solutions for BVP (1) depends on the parameter λ. In Section 4, we establish some uniqueness criteria for positive solutions for BVP (1) and show that such a positive solution x λ depends continuously on the parameter λ. In particular, we give an estimate for the critical value of the parameter λ.

          In the rest of this section, we introduce some notations and known results. For the reader’s convenience, we suggest that one refer to [2022], and [23] for details.

          Let E be a real Banach space and θ denote the zero element of E. A nonempty closed convex set P E is called a cone of E if it satisfies (i) x P , r > 0 r x P ; (ii) x P , x P x = θ . E is partially ordered by the cone P, i.e., x y iff y x P . A cone P is said to be normal if there exists a positive number N, called the normal constant of P, such that θ x y implies x N y . For u , v E , u v , denote [ u , v ] = { x E u x v } .

          For all x , y E , the notation x y means that there exist μ 1 > 0 and μ 2 > 0 such that μ 1 x y μ 2 x . Clearly, ∼ is an equivalence relation. Given e > 0 (i.e., e P and e θ ), we denote by P e the set P e = { x E x e } . It is easy to see that P e P .

          Let D E . An operator T : D E is said to be increasing if for x , y D , x y T x T y . An element x D is called a fixed point of T if T x = x .

          Lemma 1.1 (Fixed point theorem of cone expansion) [21, 22]

          Assume that Ω 1 and Ω 2 are bounded open subsets of E with θ Ω 1 Ω ¯ 1 Ω 2 . Let T : P ( Ω ¯ 2 Ω 1 ) P be a completely continuous operator such that T x x if x P Ω 1 and T x x if x P Ω 2 . Then T has a fixed point in P ( Ω ¯ 2 Ω 1 ) .

          Lemma 1.2 [23]

          Let P be a normal cone in E, T : P e P e be increasing and for all x P e and t ( 0 , 1 ) , there exists α ( t ) ( 0 , 1 ) such that T ( t x ) t α ( t ) T x . Then T has a unique fixed point x in P e . Moreover, constructing successively the sequence w n = T w n 1 ( n = 1 , 2 , ) for any w 0 P e , we have lim n + w n x = 0 .

          2 Solutions

          In what follows, set E = C [ 0 , 1 ] , the Banach space of all continuous functions on [ 0 , 1 ] with the norm x = max { | x ( t ) | t [ 0 , 1 ] } . P = { x C [ 0 , 1 ] x ( t ) 0 , t [ 0 , 1 ] } . It is clear that P is a normal cone and its normality constant is 1.

          From [18] and [19], it is evident that BVP (1) has an integral formulation given by
          x ( t ) = λ 0 1 G ( t , s ) f ( s , x ( s ) ) d s + q ( x ( 1 ) ) ( 1 2 t 2 1 6 t 3 ) ,
          (2)
          where
          G ( t , s ) = 1 6 { t 2 ( 3 s t ) , 0 t s 1 , s 2 ( 3 t s ) , 0 s t 1 .
          (3)
          It is easy to see that G ( t , s ) 0 and
          1 3 t 2 s 2 G ( t , s ) 1 2 t 2 s , t , s [ 0 , 1 ] .
          (4)
          Define operators A , B , C λ : P C [ 0 , 1 ] by
          ( A x ) ( t ) = 0 1 G ( t , s ) f ( s , x ( s ) ) d s , ( B x ) ( t ) = q ( x ( 1 ) ) ( 1 2 t 2 1 6 t 3 ) , C λ = λ A + B .

          Then A ( P ) P , B ( P ) P , and C λ ( P ) P .

          It is clear from (2) that solving BVP (1) is equivalent to finding fixed points of the operator  C λ . In particular, x is a fixed point of B iff x is a solution of the following BVP:
          { x ( 4 ) ( t ) = 0 , 0 < t < 1 , x ( 0 ) = x ( 0 ) = x ( 1 ) = x ( 1 ) + q ( x ( 1 ) ) = 0 ,
          and x is a fixed point of λA iff x is a solution of the following cantilever beam problem:
          { x ( 4 ) ( t ) = λ f ( t , x ( t ) ) , 0 < t < 1 , x ( 0 ) = x ( 0 ) = x ( 1 ) = x ( 1 ) = 0 .
          (5)
          Lemma 2.1 If x C 4 [ 0 , 1 ] satisfies
          { x ( 4 ) ( t ) 0 , t ( 0 , 1 ) , x ( 0 ) = x ( 0 ) = x ( 1 ) = 0 , x ( 1 ) 0 ,
          (6)
          then
          1. (i)

            x ( t ) is nondecreasing in t [ 0 , 1 ] , moreover, 0 x ( t ) x ( 1 ) , t [ 0 , 1 ] ;

             
          2. (ii)

            x ( t ) 0 , t [ 0 , 1 ] , that is, x ( t ) is a convex function on [ 0 , 1 ] .

             

          Proof From (6), we have x ( t ) x ( 1 ) 0 . Moreover, x ( t ) x ( 1 ) = 0 . So, x ( t ) x ( 0 ) = 0 . Thus, we complete the proof of the lemma. □

          Now, let
          K = { x P | x ( t )  is nondecreasing , x ( t ) 2 3 t 2 x ( 1 ) , t [ 0 , 1 ] } ,

          then, it is easy to show that K P is also a cone in E, and if x K , then x = x ( 1 ) .

          Lemma 2.2 C λ ( P ) K , A ( P ) K , B ( P ) K .

          Proof x P implies x ( t ) 0 , so f ( t , x ( t ) ) 0 and q ( x ( 1 ) ) 0 . Moreover, for x P ,
          ( C λ x ) ( 4 ) ( t ) = λ f ( t , x ( t ) ) 0 , t ( 0 , 1 ) , ( C λ x ) ( 0 ) = ( C λ x ) ( 0 ) = ( C λ x ) ( 1 ) = 0 , ( C λ x ) ( 1 ) = q ( x ( 1 ) ) 0 .
          By Lemma 2.1, ( C λ x ) ( t ) is convex and nondecreasing in t [ 0 , 1 ] . From (3) and (4) we have
          ( C λ x ) ( t ) 2 3 t 2 ( C λ x ) ( 1 ) λ 9 t 2 0 1 s 3 f ( s , x ( s ) ) d s + q ( x ( 1 ) ) ( 5 18 t 2 1 6 t 3 ) 0 ,

          that is, 2 3 t 2 ( C λ x ) ( 1 ) ( C λ x ) ( t ) for t [ 0 , 1 ] . Thus, we obtain C λ ( P ) K . From the above proof, we can show that A ( P ) K and B ( P ) K . This ends the proof. □

          Lemma 2.3
          1. (i)

            A : P K is a completely continuous operator;

             
          2. (ii)

            if q ( x ) is nondecreasing, then B : P K is a completely continuous operator.

             

          Proof Similarly to the proof of Theorem 1 in [19], applying the Arzela-Ascoli Theorem, the proof can be completed. □

          From the proof of Lemma 2.2 we can show the following result.

          Theorem 2.4 If x P { θ } is a solution for BVP (1), then x is a convex monotone positive solution for BVP (1).

          So, in the following sections, we only need to study solutions for BVP (1) in P { θ } .

          3 Existence and nonexistence results

          It is obvious from Lemma 2.2 that if x P { θ } is a solution for BVP (1) then x K { θ } . So in this section, we will apply Lemma 1.1 to study the existence, multiplicity and nonexistence of solutions for BVP (1) in K { θ } . It is reasonable that the domain of C λ is restricted on K. The following conditions will be assumed:

          (H1) f ( t , x ) is nondecreasing in x [ 0 , + ) for fixed t [ 0 , 1 ] ;

          (H2) q ( x ) is nondecreasing in x [ 0 , + ) ;

          (H3) F 0 : = 0 1 s 2 f ( s , 0 ) d s > 0 ;

          (H4) q ( 1 ) < 2 ;

          (H5) f : = lim x + min t [ 1 2 , 1 ] f ( t , x ) x = + ;

          (H6) q : = lim inf x + q ( x ) x > 3 .

          Set
          Λ = { λ > 0 there exists  x λ K { θ }  such that  C λ x λ = x λ }
          (7)

          and λ = sup Λ .

          Lemma 3.1 Suppose that (H1)-(H3) hold. If λ Λ , then ( 0 , λ ] Λ .

          Proof λ Λ means that there exists x λ K { θ } such that C λ x λ = x λ . Therefore, for any λ ( 0 , λ ] , we have C λ x λ C λ x λ = x λ . Set w 0 = x λ , w n = C λ w n 1 , n = 1 , 2 ,  . From (H1) and (H2) we obtain w 0 ( t ) w 1 ( t ) w n ( t ) F 0 λ 3 t 2 . By Lemma 2.3 and (H3), { w n } converges to a fixed point of C λ in K { θ } . Thus ( 0 , λ ] Λ . This completes the proof. □

          Let λ = 2 q ( 1 ) F 1 , F 1 = 0 1 s f ( s , 1 ) d s , u 0 ( t ) = F 0 λ 3 t 2 , v 0 ( t ) = t 2 and
          F = lim sup x + max t [ 0 , 1 ] f ( t , x ) x , Q = lim sup x + q ( x ) x .
          Theorem 3.2 Suppose that (H1)-(H3) hold.
          1. (i)

            If (H4) holds, then C λ has minimal and maximal fixed points in [ u 0 , v 0 ] for λ ( 0 , λ ] . Moreover, there exists λ λ > 0 such that C λ has at least one and has no fixed points in K { θ } for 0 < λ < λ and λ > λ , respectively.

             
          2. (ii)

            If F < + , Q < 2 , then when F > 0 , there exists λ 2 ( 2 Q ) F > 0 such that C λ has at least one and no fixed points in K { θ } for 0 < λ < λ and λ > λ , respectively; when F = 0 , C λ has at least one fixed point in K { θ } for λ > 0 .

             
          Proof (i) From (H1), (H3), and (H4) we have λ > 0 . For any λ ( 0 , λ ] , we obtain
          ( C λ u 0 ) ( t ) λ 3 t 2 0 1 s 2 f ( s , 0 ) d s = u 0 ( t ) , ( C λ v 0 ) ( t ) 1 2 t 2 ( λ F 1 + q ( 1 ) ) v 0 ( t ) .
          Set u n = C λ u n 1 , v n = C λ v n 1 , n = 1 , 2 ,  , then from (H1) and (H2) we have
          u 0 ( t ) u 1 ( t ) u n ( t ) v n ( t ) v 1 ( t ) v 0 ( t ) .
          (8)
          Lemma 2.3 implies that { u n } and { v n } converge to fixed points u λ and v λ of C λ , respectively. From (8) it is evident that u λ , v λ K { θ } are the minimal fixed point and maximal fixed point of C λ in [ u 0 , v 0 ] , respectively. From the definition of λ we can complete the rest of the proof.
          1. (ii)
            For any 0 < ϵ < 2 Q , there exists N 0 > 0 such that f ( t , x ) ( F + ϵ ) x and q ( x ) ( Q + ϵ ) x for x > N 0 , t [ 0 , 1 ] . Let w 0 ( t ) = 2 N 0 t 2 and λ 0 = 2 ( 2 Q ϵ ) F + ϵ , then λ 0 > 0 and
            ( C λ 0 w 0 ) ( t ) 1 2 w 0 ( t ) ( λ 0 2 ( F + ϵ ) + Q + ϵ ) w 0 ( t ) .
             

          Similarly to the proof of Lemma 3.1, we can show λ 0 Λ . The conclusion (ii) follows from Lemma 3.1 and the definition of λ . This completes the proof of Theorem 3.2. □

          Lemma 3.3 Suppose that (H1)-(H3) hold and that one of (H5) and (H6) holds. If Λ is nonempty, then
          1. (i)

            Λ is bounded from above, that is, λ < + ;

             
          2. (ii)

            λ Λ .

             

          Proof (i) Suppose to the contrary that there exists an increasing sequence { λ n } 1 + Λ such that lim n + λ n = + . Set x λ n K { θ } is a fixed point of C λ n , that is, C λ n x λ n = x λ n . There are two cases to be considered.

          Case 1. { x λ n } 1 + is bounded, that is, there exists a constant M > 0 such that x λ n M for n = 1 , 2 ,  . Hence, from (H1), (H3), and (4) we have
          M x λ n = ( C λ n x λ n ) ( 1 ) 1 3 λ n 0 1 s 2 f ( s , x λ n ( s ) ) d s F 0 3 λ n + ,

          which is a contradiction.

          Case 2. { x λ n } 1 + is unbounded, that is, there exists a subsequence of { x λ n } 1 + , still denoted by { x λ n } 1 + , such that lim n + x λ n = + .

          When (H5) holds, take L > 72 λ 1 , there exists N 1 > 0 such that f ( t , x ) L x for x N 1 , t [ 1 2 , 1 ] . Choose n 1 such that x λ n 1 > 6 N 1 . Thus, f ( t , 1 6 x λ n 1 ) 1 6 L x λ n 1 , t [ 1 2 , 1 ] . Moreover, from (H1) and the definition of K, we have
          x λ n 1 = ( C λ n 1 x λ n 1 ) ( 1 ) 1 3 λ 1 1 2 1 s 2 f ( s , 1 6 x λ n 1 ) d s > 1 72 λ 1 L x λ n 1 > x λ n 1 ,

          which is a contradiction.

          When (H6) holds, choose ϵ > 0 such that 1 3 ( q ϵ ) > 1 . There exists N 2 > 1 such that q ( x ) ( q ϵ ) x for x N 2 . Choose n 2 such that x λ n 2 > N 2 , so
          q ( x λ n 2 ( 1 ) ) = q ( x λ n 2 ) ( q ϵ ) x λ n 2 .
          Moreover,
          x λ n 2 = ( C λ n 2 x λ n 2 ) ( 1 ) 1 3 q ( x λ n 2 ( 1 ) ) 1 3 ( q ϵ ) x λ n 2 > x λ n 2 ,

          which is a contradiction.

          Consequently, we find that Λ is bounded from above.
          1. (ii)
            By the definition of λ , there exists a nondecreasing sequence { λ n } 1 + such that lim n + λ n = λ . Let x λ n K { θ } be a fixed point of C λ n . Arguing similarly as above in case 2, we can show that { x λ n } 1 + is a bounded subset in K, that is, there exists a constant M > 0 such that x λ n M , n = 1 , 2 ,  ; on the other hand, note that
            | x λ n ( t 1 ) x λ n ( t 2 ) | λ 0 1 | G ( t 1 , s ) G ( t 2 , s ) | f ( s , M ) d s + 4 3 q ( M ) | t 1 t 2 | ,
             
          we see that { x λ n } 1 + is an equicontinuous subset in K. Consequently, by an application of the Arzela-Ascoli Theorem we conclude that { x λ n } 1 + is a relatively compact set in K. So, there exists a subsequence { x λ n i } { x λ n } converging to x K . Note that
          x λ n i ( t ) = λ n i 0 1 G ( t , s ) f ( s , x λ n i ( s ) ) d s + q ( x λ n i ( 1 ) ) ( 1 2 t 2 1 6 t 3 ) .

          By taking the limit we have x ( t ) = ( C λ x ) ( t ) λ 1 3 F 0 t 2 , that is, λ Λ . The proof is complete. □

          Theorem 3.4 Suppose that (H1)-(H4) hold and that one of (H5) and (H6) holds. Then, there exists a λ λ > 0 such that BVP (1) has at least two, one, and no positive solutions for 0 < λ λ , λ < λ λ and λ > λ , respectively.

          Proof Theorem 3.2 implies ( 0 , λ ] Λ , so λ λ > 0 . From Lemmas 3.1 and 3.3, we have ( 0 , λ ] = Λ . Therefore, from the definition of λ we only to prove that C λ has at least two fixed points in K { θ } for λ ( 0 , λ ] .

          Now, given λ ( 0 , λ ] . Theorem 3.2 means that C λ has at least one fixed point x λ , 1 K { θ } which satisfies x λ , 1 1 .

          Let K 1 = { x K x < 1 } . Note that t ( 3 t ) 2 for t [ 0 , 1 ] , so for x K with x = 1 , i.e., x K 1 , we have
          C λ x = ( C λ x ) ( 1 ) 1 6 ( λ 0 1 s 2 ( 3 s ) f ( s , 1 ) d s + 2 q ( 1 ) ) 2 3 < x .
          (9)
          When (H5) holds, take L > 72 λ , there exists N 1 > 1 such that f ( t , x ) L x for x N 1 , t [ 1 2 , 1 ] . Set K 2 = { x K x < 6 N 1 } . Then K ¯ 1 K 2 . If x K 2 , we have
          C λ x = ( C λ x ) ( 1 ) λ 3 1 2 1 s 2 f ( s , 1 6 x ) d s > λ L 72 x > x .

          When (H6) holds, from the proof of Lemma 3.3 we can set K 2 = { x K x < N 2 } . Then K ¯ 1 K 2 . If x K 2 , we have C λ x = C λ x ( 1 ) 1 3 q ( x ( 1 ) ) 1 3 ( q ϵ ) x ( 1 ) > x .

          Consequently, in virtue of Lemma 1.1 we find that C λ has another fixed point x λ , 2 with
          x λ , 2 { K ¯ 2 K 1 , as (H5) holds , K ¯ 2 K 1 , as (H6) holds .

          Equation (9) implies that C λ has no fixed points in K 1 . In conclusion, for λ ( 0 , λ ] , C λ has at least two fixed points x λ , 1 and x λ , 2 in K with 0 < x λ , 1 < 1 < x λ , 2 . The proof is complete. □

          Remark 3.1 In the above results, we can replace (H5) with the following condition: there exists ϵ 0 ( 0 , 1 ) such that lim x + min t [ ϵ 0 , 1 ] f ( t , x ) x = + .

          In the following, we give some sufficient conditions that BVP (1) has no positive solutions.

          Theorem 3.5 Suppose that there exists a nonnegative integrable function a ( t ) such that f ( t , x ) a ( t ) x , t [ 0 , 1 ] , x [ 0 , + ) and a : = 0 1 s 4 ( 3 s ) a ( s ) d s > 0 . Then BVP (1) has no positive solutions for λ > 9 a .

          Proof Assume to the contrary that x λ K { θ } is a solution of BVP (1), then x λ = ( C λ x λ ) ( 1 ) 1 9 x λ λ 0 1 s 4 ( 3 s ) a ( s ) d s > x λ , which is a contradiction. The proof is complete. □

          Similarly to the proof of Theorem 3.5, we can easily obtain the following results.

          Theorem 3.6 Suppose that there exist an integrable function a 1 ( t ) 0 and a number b [ 0 , 3 ) such that f ( t , x ) a 1 ( t ) x , q ( x ) b x , t [ 0 , 1 ] , x [ 0 , + ) and a 1 : = 0 1 s 2 ( 3 s ) a 1 ( s ) d s > 0 . Then BVP (1) has no positive solutions for 0 λ < 6 2 b a 1 .

          Theorem 3.7 Suppose that q ( x ) > 3 x , x [ 0 , + ) . Then BVP (1) has no positive solutions for λ 0 .

          Remark 3.2 When q ( x ) 0 , BVP (1) becomes a cantilever beam problem (5). In this case, we can delete the conditions on q in Theorems 3.2, 3.4-3.6 and obtain the following corresponding results for BVP (5).

          Suppose that (H1) and (H3) hold. Then BVP (5) has minimal and maximal solutions in [ u 0 , v 0 ] for λ ( 0 , 2 F 1 ] . Further, if 0 < F < + , then there exists λ max { 2 F 1 , 4 F } such that BVP (5) has at least one and has no positive solutions for 0 < λ < λ and λ > λ , respectively; if F = 0 then BVP (5) has at least one positive solution for λ > 0 .

          Suppose that (H1), (H3), and (H5) hold. Then λ 2 F 1 and BVP (5) has at least two, one and has no positive solutions for 0 < λ 2 F 1 , 2 F 1 < λ λ and λ > λ , respectively.

          Under the conditions in Theorem 3.5, BVP (5) has no positive solutions for λ > 9 a .

          Suppose that a 1 ( t ) and a 1 satisfy the conditions in Theorem 3.6, then BVP (5) has no positive solutions for 0 λ < 6 a 1 .

          Remark 3.3 (i) We give an example to illustrate Theorem 3.2. Let f ( t , x ) = t 3 + 1 5 ln ( 1 + x ) , and
          q ( x ) = { sin x , 0 x π 2 , 2 π x , π 2 x π , 3 π 2 x 2 π , 2 + | sin x | , π x 3 π 2 , 4 , x 2 π .

          By straightforward calculations we see that F 0 = 1 6 , F 1 = 1 5 ( 1 + ln 2 2 ) , q ( 1 ) = sin 1 , λ = 2 q ( 1 ) F 1 7.361 , F = 1 5 , and Q = 0 . So the conditions in Theorem 3.2 are satisfied. Therefore, by Theorem 3.2 we find that there exists λ 4 F = 20 such that BVP (1) has minimal and maximal solutions in [ u 0 , v 0 ] for 0 < λ 7.361 , has at least one positive solution for 7.361 < λ < λ and has no positive solutions for λ > λ , where u 0 ( t ) = λ 18 t 2 and v 0 ( t ) = t 2 .

          We give another example to illustrate Theorem 3.4. Let f ( t , x ) = t 2 ( 1 + x 2 ) + 1 8 e t x , and
          q ( x ) = { 1 8 x 4 3 , 0 x 8 , 2 , x 8 .
          A straightforward calculation can show that F 0 = 1 8 , f = + , q ( 1 ) = 1 8 , F 1 = 11 24 , and λ = 45 11 Therefore, the conditions (H1)-(H5) hold. Thus, by Theorem 3.4 we see that there exists λ 45 11 such that BVP (1) has at least two, one, and no positive solutions for 0 < λ 45 11 , 45 11 < λ λ , and λ > λ , respectively.
          1. (ii)
            In Theorems 3.5-3.7, we do not require f and q to be monotone in x. For example, let f ( t , x ) = t x 1 + | cos x | and
            q ( x ) = { x | sin x | , 0 x 2 π , 0 , x 2 π .
             

          Take a 1 ( t ) = t , b = 1 , then the conditions in Theorem 3.6 are satisfied and a 1 = 11 20 . So by Theorem 3.6 we find that BVP (1) has no positive solutions for 0 λ < 80 11 .

          4 Uniqueness and dependence on parameter

          In this section, we will apply cone theory to further study the uniqueness of solution for BVP (1) in P { θ } and the dependence of such a positive solution on the parameter λ. The following hypotheses are needed:

          (H7) q ( 1 ) 0 and for all x [ 0 , + ) and r ( 0 , 1 ) , there exists α ( r ) ( 0 , 1 ) such that q ( r x ) r α ( r ) q ( x ) ;

          (H8) f ( t , 1 ) 0 and f ( t , r x ) r f ( t , x ) for r ( 0 , 1 ) , t [ 0 , 1 ] , x [ 0 , + ) ;

          (H9) for all t [ 0 , 1 ] , x [ 0 , + ) and r ( 0 , 1 ) , there exists β ( r ) ( 0 , 1 ) such that f ( t , r x ) r β ( r ) f ( t , x ) .

          Remark 4.1 The inequalities in (H7), (H8), and (H9) are equivalent to the following inequalities, respectively:
          q ( s x ) s α ( 1 s ) q ( x ) , s > 1 , x [ 0 , + ) , f ( t , s x ) s f ( t , x ) , s > 1 , t [ 0 , 1 ] , x [ 0 , + ) , f ( t , s x ) s β ( 1 s ) f ( t , x ) , s > 1 , t [ 0 , 1 ] , x [ 0 , + ) .

          Let e ( t ) = t 2 and define P e as in Section 1. It is obvious that P e P and if x P e then x ( 0 ) = 0 and x ( t ) > 0 , t ( 0 , 1 ] .

          Remark 4.2 (H2) and (H7) imply q ( x ) > 0 for x > 0 . Moreover, q ( x ( 1 ) ) > 0 for x P e .

          Remark 4.3 Let x λ be a solution for BVP (1) in P { θ } . If (H2) and (H7) hold, then x λ P e . Indeed, from Theorem 2.4 we have x λ ( 1 ) = x λ . So Remark 4.2 implies q ( x λ ( 1 ) ) > 0 . Note that
          q ( x λ ( 1 ) ) 3 t 2 x λ ( t ) = ( C λ x λ ) ( t ) 1 2 ( λ 0 1 s f ( s , x λ ( s ) ) d s + q ( x λ ( 1 ) ) ) t 2 ,

          we conclude x λ P e .

          So, in this section, we only need to consider the unique solution for BVP (1) in P e .

          Lemma 4.1 Assume that (H2) and (H7) hold. Then B has a unique fixed point x 0 in P e , moreover, constructing successively the sequence w n = B w n 1 ( n = 1 , 2 , ) for any initial value w 0 P e , we have lim n + w n x 0 = 0 .

          Proof For any x P e , we have 1 3 q ( x ( 1 ) ) t 2 B x ( t ) 1 2 q ( x ( 1 ) ) t 2 , which means B ( P e ) P e . For all x P e , r ( 0 , 1 ) , from (H7) we have B ( r x ) ( t ) r α ( r ) B x ( t ) . Consequently, the conclusion follows from Lemma 1.2. This completes the proof. □

          Lemma 4.2 Assume that (H1), (H2), (H7), and (H8) hold. Then
          1. (i)

            C λ : P e P e is an increasing operator;

             
          2. (ii)

            for any λ 0 and x P e , there exists φ ( λ , x ) ( 0 , 1 ) such that B x φ ( λ , x ) C λ x ;

             
          3. (iii)
            for [ u , v ] P e and r ( 0 , 1 ) , there exists η ( r , u , v ) > 0 such that
            C λ ( r x ) r ( 1 + η ( r , u , v ) ) C λ x , x [ u , v ] .
             

          Proof The conclusion (i) follows from (H1), (H2), (H7), and (4).

          The proof of (ii). For given λ 0 , x P e , from (H1) and (4) we have
          ( C λ x ) ( t ) 1 2 t 2 ( λ 0 1 s f ( s , x ) d s + q ( x ( 1 ) ) ) 3 ( λ 0 1 s f ( s , x ) d s + q ( x ( 1 ) ) 2 q ( x ( 1 ) ) B x ( t ) .
          Let
          φ ( λ , x ) = 2 q ( x ( 1 ) ) 3 ( λ 0 1 s f ( s , x ) d s + q ( x ( 1 ) ) ) ,
          (10)
          then 0 < φ ( λ , x ) < 1 and
          B x φ ( λ , x ) C λ x .
          (11)
          The proof of (iii). For any x [ u , v ] , u , v P e , from (10) and (11) we have
          B x 2 q ( x ( 1 ) ) 3 ( λ 0 1 s f ( s , x ) d s + q ( x ( 1 ) ) C λ x 2 q ( u ( 1 ) ) 3 ( λ 0 1 s f ( s , v ) d s + q ( v ( 1 ) ) ) C λ x .
          Moreover, from (H7) and (H8) we have
          C λ ( r x ) λ r A x + r α ( r ) B x r ( 1 + η ( r , u , v ) ) C λ x , r ( 0 , 1 ) , x [ u , v ] ,

          where η ( r , u , v ) = 2 ( r α ( r ) r ) q ( u ( 1 ) ) 3 r ( λ 0 1 s f ( s , v ) d s + q ( v ( 1 ) ) ) > 0 . This completes the proof. □

          Lemma 4.3 Assume that (H1), (H2), (H7), and (H8) hold. Then C λ has a unique fixed point x λ in P e iff there exists y λ P e such that C λ y λ y λ . Moreover, constructing successively the sequence w n = C λ w n 1 ( n = 1 , 2 , ) for any initial value w 0 P e , we have
          lim n + w n x λ = 0 .
          (12)

          Proof ‘⇒’ Let x λ be a fixed point of C λ in P e , i.e., C λ x λ = x λ . Taking y λ = x λ , we obtain C λ y λ y λ .

          ‘⇐’ By virtue of Lemma 4.1, B has a unique fixed point x 0 in P e . Moreover,
          x 0 C λ x 0 , λ 0 .
          (13)
          Now, we are going to prove
          x 0 y λ , λ 0 .
          (14)
          Let τ 0 = inf { τ > 0 x 0 τ y λ } , then τ 0 1 . Otherwise, τ 0 > 1 , from Lemma 4.2 we have
          x 0 C λ x 0 C λ ( τ 0 y λ ) τ 0 1 + η ( 1 τ 0 , x 0 , τ 0 y λ ) C λ y λ τ 0 1 + η ( 1 τ 0 , x 0 , τ 0 y λ ) y λ .

          By the definition of τ 0 , we get a contradiction τ 0 τ 0 1 + η ( 1 τ 0 , x 0 , τ 0 y λ ) . Thus, (14) holds.

          Set x n = C λ x n 1 , y n = C λ y n 1 , y 0 = y λ , n = 1 , 2 ,  . From (13) and (14) we have
          x 0 x 1 x n y n y 1 y 0 = y λ .
          (15)
          Lemma 2.3 implies that { x n } and { y n } converge to fixed points x and y of C λ , respectively. From (15), we have
          x 0 x 1 x n x y y n y 1 y λ .
          (16)
          To prove that C λ has only one fixed point in [ x 0 , y λ ] , let
          μ n = sup { τ > 0 x n τ y n } , n = 0 , 1 , 2 , ,
          (17)
          then
          0 < μ n 1 , x n μ n y n , n = 1 , 2 , .
          (18)
          From (16)-(18) we infer that 0 < μ 0 μ 1 μ n 1 , which means that lim n + μ n = μ 1 . We assert that μ = 1 . Otherwise, 0 < μ n μ < 1 for n 1 , then by Lemma 4.2 we deduce that
          x n + 1 C λ ( μ n y n ) C λ ( μ n μ μ y n ) μ n μ C λ ( μ y n ) μ n ( 1 + η ( μ , x 0 , y λ ) ) y n + 1 .
          By (17), we have μ n + 1 μ n ( 1 + η ( μ , x 0 , y λ ) ) , moreover, μ μ ( 1 + η ( μ , x 0 , y λ ) ) , which is a contradiction. So μ = 1 . Thus, by (16) and (18) we have
          y x y n x n ( 1 μ n ) y 0 0 as  n + ,

          which means that x = y : = x λ is the unique fixed point of C λ in [ x 0 , y λ ] .

          Now, we prove that x is the unique fixed point of C λ in P e . By the above proof, we only need to show that C λ does not have any fixed point in P e [ x 0 , y λ ] . If x ¯ is a fixed point of C λ in P e [ x 0 , y λ ] . Let
          μ ¯ = sup { τ > 0 | τ x x ¯ 1 τ x } .
          (19)
          It is evident that 0 < μ ¯ 1 . If 0 < μ ¯ < 1 , then x 0 x 1 μ ¯ x 1 μ ¯ y λ . By Lemma 4.2 we have
          μ ¯ ( 1 + η ( μ ¯ , x 0 , 1 μ ¯ y λ ) ) x C λ ( μ ¯ x ) x ¯ = C λ x ¯ C λ ( 1 μ ¯ x ) 1 μ ¯ ( 1 + η ( μ ¯ , x 0 , 1 μ ¯ y λ ) ) x .

          Thus, from (19) we have μ ¯ μ ¯ ( 1 + η ( μ ¯ , x 0 , 1 μ ¯ y λ ) ) , which is a contradiction. So μ ¯ = 1 . Moreover, x ¯ = x , which implies the contradiction: x ¯ = x [ x 0 , y λ ] and x ¯ P e [ x 0 , y λ ] .

          Finally, the iterative scheme and (12) can be proved in a similar way to the proof of Theorem 3.4 of [21], here it is omitted. The proof is complete. □

          Theorem 4.4 Assume that (H1), (H2), (H7), and (H8) hold. Then there exists a λ > 0 such that BVP (1) has a unique solution x λ in P e for λ [ 0 , λ ) and does not have any solution in P e for λ λ . Moreover, set w n = λ A w n 1 + B w n 1 ( n = 1 , 2 , ) for any w 0 P e , then (12) holds.

          Proof By Lemma 4.1, B has the unique fixed point x 0 in P e . So x 0 ( t ) = q ( x 0 ( 1 ) ) ( 1 2 t 2 1 6 t 3 ) , moreover, x 0 = x 0 ( 1 ) = 1 3 q ( x 0 ( 1 ) ) > 0 . Let ρ 0 = 1 2 0 1 s f ( s , x 0 ( 1 ) ) x 0 ( 1 ) d s , we have
          ( A x 0 ) ( t ) t 2 2 0 1 s f ( s , x 0 ( 1 ) ) d s q ( x 0 ( 1 ) ) ( 1 2 t 2 1 6 t 3 ) ρ 0 = ρ 0 x 0 ( t ) .
          (20)
          Set Δ = { λ 0  there exists  x λ P e  such that  C λ x λ = x λ } . Lemma 4.3 implies that
          Δ = { λ 0  there exists  y λ P e  such that  C λ y λ y λ } .
          (21)

          Similarly to the proof of Lemma 3.1, we can show that λ Δ implies [ 0 , λ ] Δ .

          Now, take s 0 > 1 and let λ 0 = 1 ρ 0 ( 1 s 0 α ( 1 s 0 ) 1 ) and y λ 0 = s 0 x 0 , then λ 0 > 0 and y λ 0 P e . By (H7), (H8), and (20), we have C λ 0 y λ 0 λ 0 s 0 ρ 0 x 0 + s 0 α ( 1 s 0 ) x 0 y λ 0 , that is, λ 0 Δ . Moreover, [ 0 , λ 0 ] Δ .

          Let λ = sup Δ , then λ λ 0 > 0 . We assert that λ Λ . Indeed, if λ = + , from the definition of λ it is obvious that λ Λ . Suppose that λ < + and λ Λ . Then by (14) and (21) there exists x 0 y λ P e such that C λ y λ y λ . Similarly to the proof of (20), we have
          ( A y λ ) ( t ) ( 1 2 0 1 s f ( s , y λ ) x 0 ( 1 ) d s ) x 0 ( t ) ( 1 2 0 1 s f ( s , y λ ) x 0 ( 1 ) d s ) ( B y λ ) ( t ) .
          Denote ρ 1 = 1 2 0 1 s f ( s , y λ ) x 0 ( 1 ) d s , then
          0 < ρ 1 < + and A y λ ρ 1 B y λ .
          (22)
          Set v = s 1 y λ for given s 1 > 1 , then v P e . Since s 1 α ( 1 s 1 ) 1 < 1 , we can choose δ > 0 such that s 1 α ( 1 s 1 ) 1 < 1 δ ρ 1 . Therefore, from (22) we have
          C λ + δ ( v ) ( λ + δ ) s 1 A y λ + s 1 α ( 1 s 1 ) B y λ s 1 ( λ A y λ + δ ρ 1 B y λ + B y λ δ ρ 1 B y λ ) v .

          This means that λ + δ Δ , which is a contradiction to the definition of λ . So, Δ = [ 0 , λ ) . Consequently, an application of Lemma 4.3 completes the proof. □

          In what follows, we assume that x 0 is the unique fixed point of B in P e , x λ is the unique fixed point of C λ in P e and λ = sup Δ .

          Theorem 4.5 Assume that (H1), (H2), (H7), and (H8) hold. Then x λ depends upon the parameter λ as follows:
          1. (i)

            x λ is nondecreasing with respect to λ for λ [ 0 , λ ) ;

             
          2. (ii)

            x λ is continuous with respect to λ for λ [ 0 , λ ) ;

             
          3. (iii)

            lim λ 0 + x λ x 0 = 0 and lim λ λ 0 x λ = + .

             

          Proof (i) Let λ 1 , λ 2 [ 0 , λ ) with λ 1 λ 2 . Since C λ 1 x λ 2 C λ 2 x λ 2 = x λ 2 , from the proof of Lemma 4.3, we find that the unique fixed x λ 1 of C λ 1 belongs to [ x 0 , x λ 2 ] , which means that x λ 1 x λ 2 .

          (ii)Let λ 0 ( 0 , λ ) . In order to prove lim λ λ 0 x λ 0 x λ = 0 , let sequence { λ n } satisfy
          0 < λ 1 λ 2 λ n λ 0 and lim n + λ n = λ 0 .
          By virtue of the above conclusion (i) we have
          x λ 1 x λ 2 x λ n x λ 0 ,
          (23)
          which implies that { x λ n } is a bounded subset in P. Further, similarly to the proof of the conclusion (ii) in Lemma 3.3 we see that { x λ n } converges to x P . From (23) we have x [ x λ 1 , x λ 0 ] , which leads to x P e . Note that
          x λ n = λ n A x λ n + B x λ n .

          By taking the limit we have x = λ 0 A x + B x = C λ 0 x . Since C λ 0 has only one fixed point in P e , then x = x λ 0 . This means that x λ 0 x λ 0 as λ λ 0 .

          A similar argument can show that for any λ 0 [ 0 , λ ) , x λ x λ 0 0 as λ λ 0 + . Thus, the proof of (ii) is complete.
          1. (iii)

            It is obvious from the above conclusion (ii) that lim λ 0 + x λ x 0 = 0 .

             

          In order to finish the proof of lim λ λ 0 x λ = + , we consider two cases.

          Case 1. λ = + .

          Since x λ = λ A x λ + B x λ λ A x 0 , then x λ λ A x 0 , which means lim λ λ 0 x λ = + .

          Case 2. λ < + .

          By the above conclusion (i) we have lim λ λ 0 x λ + . Suppose to the contrary that lim λ λ 0 x λ < + . Similarly to the case 2 in the proof of Lemma 3.3, we conclude that C λ has a fixed point x P { θ } . From Remark 4.3 we have x P e . So λ [ 0 , λ ) , which is a contradiction. This ends the proof. □

          Now, we give an estimate for critical value λ in Theorem 4.4. If (H1) and (H8) hold, then
          f ( t , x ) x f ( t , 1 ) max t [ 0 , 1 ] f ( t , 1 ) , x > 1 , t [ 0 , 1 ] .

          Moreover, F = lim sup x + max t [ 0 , 1 ] f ( t , x ) x [ 0 , + ) .

          Theorem 4.6 Assume that (H1), (H2), (H7), and (H8) hold. Then
          λ { 2 F , 0 < F < + , = + , F = 0 .
          (24)
          Proof For any ϵ > 0 , there exists r 0 ( 0 , 1 ) such that
          q ( 1 ) 1 r 0 and f ( t , 1 r ) 1 r ( F + ϵ ) , r r 0 , t [ 0 , 1 ] ,
          (25)
          Note that r 0 α ( r 0 ) r 0 > 1 , we can choose a sufficiently large positive integer number k such that ( r 0 α ( r 0 ) r 0 ) k 1 r 0 , that is,
          ( 1 r 0 α ( r 0 ) ) k 1 r 0 k 1 .
          (26)
          Let w ( t ) = ( 1 r 0 ) k e ( t ) , then, from (4), (25), and (26) we have
          ( A w ) ( t ) t 2 2 0 1 s f ( s , 1 r 0 k ) d s t 2 2 r 0 k 1 0 1 s f ( s , 1 r 0 ) d s 1 4 ( F + ϵ ) w ( t ) , ( B w ) ( t ) t 2 2 q ( 1 r 0 k ) t 2 2 ( 1 r 0 α ( r 0 ) ) q ( 1 r 0 k 1 ) t 2 2 ( 1 r 0 α ( r 0 ) ) k q ( 1 ) t 2 2 ( 1 r 0 ) k = 1 2 w ( t ) .
          Moreover, taking λ ϵ = 2 F + ϵ , we have
          ( C λ ϵ w ) ( t ) = λ ϵ ( A w ) ( t ) + ( B w ) ( t ) 1 4 λ ϵ ( F + ϵ ) w ( t ) + 1 2 w ( t ) w ( t ) .

          Consequently, from (21) we obtain λ ϵ = 2 F + ϵ [ 0 , λ ) , that is, λ > 2 F + ϵ , which implies that (24) holds. This completes the proof. □

          Remark 4.4 Different from Theorems 3.2 and 3.4, the estimate of λ in Theorem 4.6 does not take into account effect of q ( x ) . This is valuable, because the conditions (H2) and (H7) cannot ensure Q < 2 as lim sup r 0 α ( r ) = 1 . Certainly, if Q < 2 , then λ 2 ( 2 Q ) F . In particular, if Q = 0 , then λ 4 F .

          Corollary 4.7 Assume that (H1), (H2), (H7), and (H9) hold. Then
          1. (i)

            BVP (1) has a unique positive solution x λ in P e for λ [ 0 , + ) . Moreover, for any w 0 P e , set w n = λ A w n 1 + B w n 1 ( n = 1 , 2 , ), then lim n + w n x λ = 0 ;

             
          2. (ii)

            x λ is nondecreasing with respect to λ for λ [ 0 , + ) ;

             
          3. (iii)

            x λ is continuous with respect to λ for λ [ 0 , + ) ;

             
          4. (iv)

            lim λ 0 + x λ x 0 = 0 and lim λ + x λ = + .

             
          Proof From (H1), (H2), (H7), and (4), we see that C λ : P e P e is increasing for any given λ 0 . Further, for any given λ 0 we have
          C λ ( r x ) = λ A ( r x ) + B ( r x ) r δ ( r ) C λ x , x P e , r ( 0 , 1 ) ,

          where δ ( r ) = max { α ( r ) , β ( r ) } . Thus, the conclusion (i) follows from Lemma 1.2.

          From (H9), we have f ( t , r x ) r f ( t , x ) for r ( 0 , 1 ) , t [ 0 , 1 ] and x [ 0 , + ) . Therefore, in the same way as in the proof of Theorem 4.5, we can complete the rest of the proof. □

          When q ( x ) c > 0 is a constant function, Q = 0 and B x ( t ) = c ( 1 2 t 2 1 6 t 3 ) : = x 0 ( t ) . It is evident that B satisfies (H2) and (H7). So we can obtain the following two results.

          Corollary 4.8 Assume that (H1) and (H8) hold. If F > 0 , then
          1. (i)

            there exists λ 4 F > 0 such that BVP (1) with q ( x ) c has a unique positive solution x λ in P e for λ [ 0 , λ ) and does not have any solution in P e for λ λ . Moreover, for any w 0 P e , set w n = x 0 + λ A w n 1 ( n = 1 , 2 , ), then lim n + w n x λ = 0 ;

             
          2. (ii)

            x λ is nondecreasing with respect to λ for λ [ 0 , λ ) ;

             
          3. (iii)

            x λ is continuous with respect to λ for λ [ 0 , λ ) ;

             
          4. (iv)

            lim λ 0 + x λ x 0 = 0 and lim λ λ x λ = + .

             
          Corollary 4.9 Assume that (H1) and (H8) hold. If F = 0 , then
          1. (i)

            for any λ [ 0 , + ) , BVP (1) with q ( x ) c has a unique positive solution x λ in P e , moreover, for any w 0 P e , set w n = x 0 + λ A w n 1 ( n = 1 , 2 , ), then lim n + w n x λ = 0 ;

             
          2. (ii)

            x λ is nondecreasing in λ for λ [ 0 , + ) ;

             
          3. (iii)

            x λ is continuous with respect to λ for λ [ 0 , + ) ;

             
          4. (iv)

            lim λ 0 + x λ x 0 = 0 and lim λ + x λ = + .

             

          Corollary 4.10 Assume that (H1) and (H9) hold. Then the conclusions (i), (ii), (iii), and (iv) in Corollary  4.9 hold.

          Finally, we give two concrete examples to illustrate those results in the section.

          Example 1 In BVP (1), let
          f ( t , x ) = { t 3 x , 0 x 1 , t 6 ( x + x ) , x > 1 and q ( x ) = { x 3 5 , 0 x 32 , 8 , x > 32 ,

          it is obvious that the conditions (H1) and (H2) are satisfied. For any r ( 0 , 1 ) ,

          as 0 x 1 , we have f ( t , r x ) = t r 3 x = r f ( t , x ) ;

          as x > 1 and 0 < r x 1 , we have f ( t , r x ) = t r 3 x r t 3 ( 1 2 x + 1 2 x ) t r 6 ( x + x ) = r f ( t , x ) ;

          as x > 1 and r x > 1 , we have f ( t , r x ) = t 6 ( r x + r x ) t r 6 ( x + 1 r x ) r f ( t , x ) ,

          that is, f ( t , r x ) r f ( t , x ) for x [ 0 , + ) and t [ 0 , 1 ] . Similarly, we can obtain q ( r x ) r 3 5 q ( x ) for x [ 0 , + ) . Therefore, the conditions (H7) and (H8) are satisfied. Note that
          F = lim sup x + max t [ 0 , 1 ] f ( t , x ) x = 1 6 , Q = lim sup x + q ( x ) x = 0 .

          By Theorems 4.4, 4.5 and Remarks 4.3, 4.4 we see that there exists λ 24 such that BVP (1) has a unique positive solution x λ for λ [ 0 , λ ) and does not have any positive solution for λ λ . Moreover, for any w 0 P e , set w n ( t ) = λ A w n 1 ( t ) + B w n 1 ( t ) ( n = 1 , 2 , ), then lim n w n x λ = 0 , and such solution x λ ( t ) satisfies the properties (i), (ii), and (iii) in Theorem 4.5.

          Example 2 In BVP (1), let f ( t , x ) = t ( 1 t ) x 1 + x , q ( x ) = 1 , t [ 0 , 1 ] , x [ 0 , + ) , it is easy to see that (H1) holds. For any r ( 0 , 1 ) , we have
          f ( r x ) = t ( 1 t ) r x 1 + r x r t ( 1 t ) x 1 + x r f ( t , x ) , x [ 0 , + ) .
          So, (H8) holds. Note that
          F = lim sup x + max t [ 0 , 1 ] f ( t , x ) x = 0 ,

          by Corollary 4.9 we find that BVP (1) has a unique positive solution x λ for λ 0 . Moreover, for any w 0 P e , set w n ( t ) = 1 2 t 2 1 6 t 3 + λ A w n 1 ( t ) ( n = 1 , 2 , ), then lim n w n x λ = 0 , and such a solution x λ ( t ) satisfies the properties (ii), (iii), and (iv) in Corollary 4.9 with x 0 ( t ) = 1 2 t 2 1 6 t 3 .

          In this example, by using Wolfram Mathematica 9.0, we can plot the graphs of solutions x λ ( t ) for BVP (1) with λ = 0 , 3 , 10 , 15 , 30 , 50 , as the Figure 1 shows.
          http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2014-80/MediaObjects/13661_2013_Article_708_Fig1_HTML.jpg
          Figure 1

          Solutions for BVP ( 1 ) with f ( t , x ) = t ( 1 t ) x 1 + x and q ( x ) = 1

          Declarations

          Acknowledgements

          The authors sincerely thank the reviewers for their valuable suggestions and useful comments. This research was supported by the NNSF of China (11361047), the University Natural Science Research Develop Foundation of Shanxi Province of China (20111021, 2013156), Research Project Supported by Shanxi Scholarship Council of China (2013-102) and the Science Foundation of Qinghai Province of China (2012-Z-910).

          Authors’ Affiliations

          (1)
          Department of Mathematics, Taiyuan Normal University

          References

          1. Aftabizadeh AR: Existence and uniqueness theorems for fourth-order boundary value problems. J. Math. Anal. Appl. 1986, 116: 415-426. 10.1016/S0022-247X(86)80006-3MATHMathSciNetView Article
          2. Agarwal RP, Chow YM: Iterative methods for a fourth order boundary value problem. J. Comput. Appl. Math. 1984, 10: 203-217. 10.1016/0377-0427(84)90058-XMATHMathSciNetView Article
          3. Gupta CP: Existence and uniqueness results for a bending of an elastic beam equation at resonance. J. Math. Anal. Appl. 1988, 135: 208-225. 10.1016/0022-247X(88)90149-7MATHMathSciNetView Article
          4. Bai Z, Wang H: On positive solutions of some nonlinear fourth-order beam equations. J. Math. Anal. Appl. 2002, 270: 357-368. 10.1016/S0022-247X(02)00071-9MATHMathSciNetView Article
          5. Bai Z: The upper and lower solution method for some fourth-order boundary value problems. Nonlinear Anal. 2007, 67(6):1704-1709. 10.1016/j.na.2006.08.009MATHMathSciNetView Article
          6. Bonanno G, Bellaa BD: A boundary value problem for fourth-order elastic beam equations. J. Math. Anal. Appl. 2008, 343: 1166-1176. 10.1016/j.jmaa.2008.01.049MATHMathSciNetView Article
          7. Li Y: Positive solutions of fourth-order boundary value problems with two parameters. J. Math. Anal. Appl. 2003, 281: 477-484. 10.1016/S0022-247X(03)00131-8MATHMathSciNetView Article
          8. Liu XL, Li WT: Positive solutions of the nonlinear fourth-order beam equation with three parameters. J. Math. Anal. Appl. 2005, 303: 150-163. 10.1016/j.jmaa.2004.08.026MATHMathSciNetView Article
          9. Liu B: Positive solutions of fourth-order two point boundary value problems. Appl. Math. Comput. 2004, 148: 407-420. 10.1016/S0096-3003(02)00857-3MATHMathSciNetView Article
          10. Ma RY, Xu L: Existence of positive solutions of a nonlinear fourth-order boundary value problem. Appl. Math. Lett. 2010, 23: 537-543. 10.1016/j.aml.2010.01.007MATHMathSciNetView Article
          11. Ma RY, Thompson B: Nodal solutions for a nonlinear fourth-order eigenvalue problem. Acta Math. Sin. Engl. Ser. 2008, 24(1):27-34. 10.1007/s10114-007-1009-6MATHMathSciNetView Article
          12. Yang B: Positive solutions for a fourth order boundary value problem. Electron. J. Qual. Theory Differ. Equ. 2005, 2005(3):1-17.View Article
          13. Zhang X: Existence and iteration of monotone positive solutions for an elastic beam with a corner. Nonlinear Anal., Real World Appl. 2009, 10: 2097-2103. 10.1016/j.nonrwa.2008.03.017MATHMathSciNetView Article
          14. Graef JR, Qian C, Yang B: A three point boundary value problem for nonlinear fourth order differential equations. J. Math. Anal. Appl. 2003, 287: 217-233. 10.1016/S0022-247X(03)00545-6MATHMathSciNetView Article
          15. Yao QL: Existence and multiplicity of positive solutions to a singular elastic beam equation rigidly fixed at both ends. Nonlinear Anal. 2008, 69: 2683-2694. 10.1016/j.na.2007.08.043MATHMathSciNetView Article
          16. Yao QL: Local existence of multiple positive solutions to a singular cantilever beam equation. J. Math. Anal. Appl. 2010, 363: 138-154. 10.1016/j.jmaa.2009.07.043MATHMathSciNetView Article
          17. Ma TF: Positive solutions for a beam equation on a nonlinear elastic foundation. Math. Comput. Model. 2004, 39: 1195-1201. 10.1016/j.mcm.2004.06.001MATHView Article
          18. Li SY, Zhang XQ: Existence and uniqueness of monotone positive solutions for an elastic beam equation with nonlinear boundary conditions. Comput. Math. Appl. 2012, 63: 1355-1360. 10.1016/j.camwa.2011.12.065MATHMathSciNetView Article
          19. Alves E, Ma TF, Pelicer ML: Monotone positive solutions for a fourth order equation with nonlinear boundary conditions. Nonlinear Anal. 2009, 71: 3834-3841. 10.1016/j.na.2009.02.051MATHMathSciNetView Article
          20. Amann H: Fixed point equations and nonlinear eigenvalue problems in ordered Banach spaces. SIAM Rev. 1976, 18: 602-709.MathSciNetView Article
          21. Guo DJ, Lakshmikantham V: Nonlinear Problems in Abstracts Cone. Academic Press, New York; 1988.
          22. Deimling K: Nonlinear Functional Analysis. Springer, Berlin; 1985.MATHView Article
          23. Zhai CB, Yang C, Guo CM: Positive solutions of operator equations on ordered Banach spaces and applications. Comput. Math. Appl. 2008, 56: 3150-3156. 10.1016/j.camwa.2008.09.005MATHMathSciNetView Article

          Copyright

          © Wang et al.; licensee Springer. 2014

          This article is published under license to BioMed Central Ltd. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly credited.